The Herpes Zoster Patient Pathway and Gaps in Current Vaccination Guidelines in Southeast Asia: Summary of a Zoster Experts’ Network Scientific Workshop - Gyneth Lourdes G. Bibera; Peter San Martin; Desiree A. M. van Oorschot; Afif Nurul Hidayati; Deliana Permatasari; Sasheela Sri La Sri Ponnampalavanar; Kughan Govinden; Maria Christina Filomena Batac; Joselito Javier; Terapong Tantawichien; Phatu Boonmahittisut; Trinh Minh Trang; et al. (Vaccines)
The burden of herpes zoster (HZ) is recognized worldwide; however, there is seemingly limited information on incidence and vaccination practices in Southeast Asia (SEA). A scientific workshop was held by the Zoster Experts’ Network to exchange and consolidate insights on the burden of HZ and the patient pathway in SEA. The workshop included practicing clinical experts and public health specialists/epidemiologists from Indonesia, Malaysia, the Philippines, Thailand, and Vietnam. It aimed to identify gaps in the literature, outline patient pathways, and evaluate HZ vaccine recommendations among these countries. Consensus was identified on the substantial lack of epidemiological data on HZ in SEA and the need to investigate the impact of age, immunocompromising conditions, and comorbidities on the incidence and severity of HZ in the region. However, available data in SEA did indicate a rising disease and socioeconomic burden of HZ, with concerns that current treatment strategies for HZ are suboptimal. The HZ patient pathways generated by the experts highlighted common themes and differences between the five countries. Furthermore, the experts highlighted the lack of awareness of HZ and its impact on patients’ quality of life, among patients and healthcare professionals. Evaluation of the current local HZ vaccine recommendations further showed differences in age and the inclusion of at-risk populations between countries. The workshop outcomes emphasize the need for further HZ surveillance in SEA. Efforts to align and address leakage within the patient pathway and raise awareness on the impact of HZ should be prioritized. Awareness initiatives and alignment on vaccine recommendations are also needed.